Identifying Patient Characteristics Associated With Opioid Use to Inform Surgical Pain Management - Anish K. Agarwal, MD, MPH, MS; Ruiying Xiong, MS; Jeffrey Ebert, PhD; Fran Shofer, PhD; Evan Spencer, MS; Daniel Lee, MD, MS; Zarina Ali, MD, MS; M. Kit Delgado, MD, MS (Annals of Surgery Open)
Objective:. Balancing surgical pain management and opioid stewardship is complex. Identifying patient-level variables associated with low or no use can inform tailored prescribing. Methods:. A prospective, observational study investigating surgical procedures, prescription data, and patient-reported outcomes at an academic health system in Pennsylvania. Surgical patients were consented following surgery, and prospective data were captured using automated text messaging (May 1, 2021–February 29, 2022). The primary outcome was opioid use. Results:. Three thousand six hundred three (30.2%) patients consented. Variation in patient reported used included 28.1% of men reported zero use versus 24.3% of women, 20.5% of Black patients reported zero use versus 27.2% of white patients. Opioid-naïve patients reported more zero use as compared with chronic use (29.7% vs 9.8%). Patients reporting higher use had more telephone calls and office visits within 30 days but no change in emergency department utilization or admissions. Higher discharge pain score was associated with higher use. In the adjusted analysis of opioid use relative to the guideline, higher use was associated with age, male sex, obesity, discharge pain score, and history of mental health disorder. In the adjusted model, younger age and being opioid naïve were associated with low to zero use across procedures. Conclusions:. Younger age, being opioid-naïve, and lower discharge pain score are associated with low or no postoperative opioid use. These characteristics can be used by clinicians to help tailor opioid prescribing to specific patients to reduce the risk of prolonged exposure and unused tablets in the community.